Reconsidering John Calvin - Zachman, Randall C. (Current issues in theology, 2012)
Randall C. Zachman places Calvin in conversation with theologians such as Pascal, Kierkegaard, Ezra the Scribe, Julian of Norwich and Karl Barth, and attends to themes in Calvin's theology which are often overlooked. Zachman draws out Calvin's use of astronomy and great concern to see ourselves in comparison to the immensity of the universe, acknowledging in wonder and awe our nothingness before God. Throughout, Zachman presents a Calvin who seeks a route out of self-deception to self-knowledge, though Kierkegaard shows that it is love, and not judgment, that most deeply reveals us to ourselves. The book discusses Calvin's understanding of the election of the Jews and their relationship to God, and further reconsiders Calvin's understanding of judgment and how the call to love our neighbour is undermined by the formation of alliances.